Psychological aspects of getting education in life-threatening conditions - Astashenkova, S. O. (Запорізький державний медико-фармацевтичний університет, 2023)
The aim of the research: To study the psychological aspects of the educational process in life-threatening conditions.
Keywords: тези доповідей